Students Engagement and Motivation in Gamified Learning - Mihaela Covrig; Simona Irina Goia (Agoston); Ramona Stefania Igret; Cristian Virgil Marinas; Alexandra Dorina Miron; Monica Roman (Amfiteatru Economic, 2023)
Recently, technology has been increasingly integrated into higher education through gamified learning, which applies game design principles to educational content. The purpose of the present paper is to assess and depict the engagement of students in the field of economics and business in gamified learning and to understand the relationship between engagement and motivation in gamified learning, elements less studied in the context of economics and business higher education, as shown in the literature. The paper proposes an original approach both in terms of the research method and the context of the study. In order to analyse engagement in gamified learning, we use Nicola Whitton's scale and employ an exploratory factor analysis on data collected through a questionnaire-based survey distributed among students at one of the largest universities of economics and business in Romania, namely The Bucharest University of Economic Studies (BUES). The analysis reveals three specific engagement factors: the first factor represents interest in new challenges; the second factor reflects immersion in gamified learning and satisfaction of completing; the third factor is related to students' purposes and clarity of the goals. Our results show that all factors exhibit positive associations with student learning motivation, while the first factor also indicates an association with the gender of the respondents. A good understanding of these factors can contribute to improving the teaching process by integrating gamification into teaching activities.
Keywords: A2; A23; I21; 330; gamified learning; learning motivation; engagement; internship; skills; higher education.